Development of palm oil-cattle integration program to support self-sufficiency of beef and development of human resources - Djatmiko Pinardi; Daru Mulyono; Dimar Sari Wahyuni; Maman Surachman (Faculty of Animal Science, Universitas Brawijaya, 2020)
The research aims to provide input (suggestions) to the government especially in the development of the Palm Oil-Cattle Integration Program (PCIP) to increase beef production and human resources development. This research is analytical descriptive research with information and primary data was gathered through various methods such as audience with key informants and focus group discussion. Secondary data was gathered through scientific publication review. Data analysis was conducted to predict both national beef production and consumption by using a trend-damped exponential forecasting model. The result of the research shows that national beef production 2018-2045 is projected to increase with an annual average growth rate of 1.19%, while national beef consumption increase with an annual average growth rate of 2.34%. The development of beef cattle through PCIP is prospective. The major problems faced by cattle ranchers today are the lack of livestock grazing and limited livestock feed. PCIP offers the solution to fulfill the need for cattle from the potential biomass which can be used as feed materials which is available throughout the year regardless of the season. Moreover, several types of weeds that contain high nutrients and resistant to shade which potential for Cattles feed materials could be planted under the oil palm plantation. It is estimated that by 2034 the gradual development of PCIP reaches up to 2,150,000 ha, Indonesia will be able to achieve national beef self-sufficiency and expected will impact to increasing quality of human resources.